Subchronic exposures to fungal bioaerosols promotes allergic pulmonary inflammation in naïve mice - Nayak, Ajay P. (Clin Exp Allergy, 2016)
BACKGROUND: Epidemiological surveys indicate that occupants of mold contaminated environments are at increased risk of respiratory symptoms. The immunological mechanisms associated with these responses require further characterization. OBJECTIVE: The aim of this study was to characterize the immunotoxicological outcomes following repeated inhalation of dry Aspergillus fumigatus spores aerosolized at concentrations potentially encountered in contaminated indoor environments. METHODS: A. fumigatus spores were delivered to the lungs of naïve BALB/cJ mice housed in a multi-animal nose-only chamber twice a week for a period of 13 weeks. Mice were evaluated at 24 and 48 hours post-exposure for histopathological changes in lung architecture, recruitment of specific immune cells to the airways, and serum antibody responses. RESULT: Germinating A. fumigatus spores were observed in lungs along with persistent fungal debris in the perivascular regions of the lungs. Repeated exposures promoted pleocellular infiltration with concomitant epithelial mucus hypersecretion, goblet cell metaplasia, subepithelial fibrosis and enhanced airway hyperreactivity. Cellular infiltration in airways was predominated by CD4(+) T cells expressing the pro-allergic cytokine IL-13. Furthermore, our studies show that antifungal T cell responses (IFN-γ(+) or IL-17A(+)) co-expressed IL-13, revealing a novel mechanism for the dysregulated immune response to inhaled fungi. Total IgE production was augmented in animals repeatedly exposed to A. fumigatus. CONCLUSIONS & CLINICAL RELEVANCE: Repeated inhalation of fungal aerosols resulted in significant pulmonary pathology mediated by dynamic shifts in specific immune populations and their cytokines. These studies provide novel insights into the immunological mechanisms and targets that govern the health outcomes that result from repeated inhalation of fungal bioaerosols in contaminated environments.